548–480 Ma plate motions in the Adelaide Orogen record coeval interactions between proximal (W–E) and distal (N–S) plates, producing arc formation and trench rollback - Timothy H. Bell; Clement Fay (Gondwana Research, 2026)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Inhibition of fatty acid binding protein-5 in the basolateral amygdala induces anxiolytic effects and accelerates fear memory extinction - Matthew J. Jones; Taygun C. Uzuneser; Timothy Clement; Hehe Wang; Iwao Ojima; Walter J. Rushlow; Steven R. Laviolette (Psychopharmacology, 2024)

Hydrology drives export and composition of carbon in a pristine tropical river - Travis W. Drake; Matti Barthel; Christian Ekemba Mbongo; Davin Mata Mpambi; Simon Baumgartner; Clement Ikene Botefa; Marijn Bauters; Martin R. Kurek; Robert G. M. Spencer; Amy M. McKenna; Negar Haghipour; Godé Lompoko Ekamba; et al. (Limnology and Oceanography, 2023)
The Ruki is a pristine blackwater tributary in the Congo Basin draining tropical lowland forest. Daily discharge and fortnightly concentrations, isotopic ratios, and molecular composition of carbon and organic matter were measured for 1 yr (2019–2020). Like the Congo River, discharge peaked from November–January, with a smaller secondary peak in June. Dissolved organic carbon (DOC), inorganic carbon (DIC), carbon dioxide ( p CO 2 ), and methane ( p CH 4 ) concentrations were high (21.3 ± 4.8 mg C L −1 , 5.8 ± 0.9 mg C L −1 , 6370 ± 1740 ppm, and 250 ± 100 ppm, respectively) and positively correlated with discharge, indicating transport limitation. Total suspended solids and particulate organic carbon (POC) concentrations were generally low (3.68 ± 1.61 mg L −1 , 0.88 ± 0.33 mg C L −1 , respectively) and varied inversely with discharge, indicating source limitation. The Ruki exported a total of 3.25 Tg C yr −1 , of which DOC, DIC, and POC comprised 76%, 20%, and 3%, respectively. This DOC flux represents ~ 20% of the annual Congo Basin flux from about 5% of its area, highlighting the high yield. Isotopic ratios of DOC and POC indicate modern C3 forest vegetation as a source, except for a few older samples potentially indicating peat inputs. The bulk molecular composition of dissolved organic matter was seasonally consistent; however, a more oxidized and aromatic assemblage occurred at high discharge, corresponding with forest vegetation, while a more aliphatic, nitrogen‐, and sulfur‐enriched assemblage was found during low discharge, corresponding with soil‐derived organic matter. Overall, these results underscore how hydrology controls C concentrations in the Ruki River and how this blackwater river contributes disproportionately to C export per unit area within the Congo Basin hydrosystem.

Analytical approaches for screening of per- and poly fluoroalkyl substances in food items: A review of recent advances and improvements - Olutobi Daniel Ogunbiyi; Timothy Oladiran Ajiboye; Elizabeth Oyinkansola Omotola; Peter Olusakin Oladoye; Clement Ajibade Olanrewaju; Natalia Quinete (Environmental Pollution, 2023)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

The case for increasing the statistical power of eddy covariance ecosystem studies: why, where and how? - Timothy Hill; Melanie Chocholek; Robert Clement (Global Change Biology, 2017)
Eddy covariance ( EC ) continues to provide invaluable insights into the dynamics of Earth's surface processes. However, despite its many strengths, spatial replication of EC at the ecosystem scale is rare. High equipment costs are likely to be partially responsible. This contributes to the low sampling, and even lower replication, of ecoregions in Africa, Oceania (excluding Australia) and South America. The level of replication matters as it directly affects statistical power. While the ergodicity of turbulence and temporal replication allow an EC tower to provide statistically robust flux estimates for its footprint, these principles do not extend to larger ecosystem scales. Despite the challenge of spatially replicating EC , it is clearly of interest to be able to use EC to provide statistically robust flux estimates for larger areas. We ask: How much spatial replication of EC is required for statistical confidence in our flux estimates of an ecosystem? We provide the reader with tools to estimate the number of EC towers needed to achieve a given statistical power. We show that for a typical ecosystem, around four EC towers are needed to have 95% statistical confidence that the annual flux of an ecosystem is nonzero. Furthermore, if the true flux is small relative to instrument noise and spatial variability, the number of towers needed can rise dramatically. We discuss approaches for improving statistical power and describe one solution: an inexpensive EC system that could help by making spatial replication more affordable. However, we note that diverting limited resources from other key measurements in order to allow spatial replication may not be optimal, and a balance needs to be struck. While individual EC towers are well suited to providing fluxes from the flux footprint, we emphasize that spatial replication is essential for statistically robust fluxes if a wider ecosystem is being studied.

Quantifying landscape‐level methane fluxes in subarctic Finland using a multiscale approach - Iain. P. Hartley; Timothy. C. Hill; Thomas. J. Wade; Robert. J. Clement; John. B. Moncrieff; Ana. Prieto‐Blanco; Mathias. I. Disney; Brian. Huntley; Mathew. Williams; Nicholas. J. K. Howden; Philip. A. Wookey; Robert. Baxter (Global Change Biology, 2015)
Quantifying landscape‐scale methane ( CH 4 ) fluxes from boreal and arctic regions, and determining how they are controlled, is critical for predicting the magnitude of any CH 4 emission feedback to climate change. Furthermore, there remains uncertainty regarding the relative importance of small areas of strong methanogenic activity, vs. larger areas with net CH 4 uptake, in controlling landscape‐level fluxes. We measured CH 4 fluxes from multiple microtopographical subunits (sedge‐dominated lawns, interhummocks and hummocks) within an aapa mire in subarctic Finland, as well as in drier ecosystems present in the wider landscape, lichen heath and mountain birch forest. An intercomparison was carried out between fluxes measured using static chambers, up‐scaled using a high‐resolution landcover map derived from aerial photography and eddy covariance. Strong agreement was observed between the two methodologies, with emission rates greatest in lawns. CH 4 fluxes from lawns were strongly related to seasonal fluctuations in temperature, but their floating nature meant that water‐table depth was not a key factor in controlling CH 4 release. In contrast, chamber measurements identified net CH 4 uptake in birch forest soils. An intercomparison between the aerial photography and satellite remote sensing demonstrated that quantifying the distribution of the key CH 4 emitting and consuming plant communities was possible from satellite, allowing fluxes to be scaled up to a 100 km 2 area. For the full growing season (May to October), ~ 1.1–1.4 g CH 4 m −2 was released across the 100 km 2 area. This was based on up‐scaled lawn emissions of 1.2–1.5 g CH 4 m −2 , vs. an up‐scaled uptake of 0.07–0.15 g CH 4 m −2 by the wider landscape. Given the strong temperature sensitivity of the dominant lawn fluxes, and the fact that lawns are unlikely to dry out, climate warming may substantially increase CH 4 emissions in northern Finland, and in aapa mire regions in general.

Evidence for strong seasonality in the carbon storage and carbon use efficiency of an Amazonian forest - Lucy Rowland; Timothy Charles Hill; Clement Stahl; Lukas Siebicke; Benoit Burban; Joana Zaragoza‐Castells; Stephane Ponton; Damien Bonal; Patrick Meir; Mathew Williams (Global Change Biology, 2014)
The relative contribution of gross primary production and ecosystem respiration to seasonal changes in the net carbon flux of tropical forests remains poorly quantified by both modelling and field studies. We use data assimilation to combine nine ecological time series from an eastern Amazonian forest, with mass balance constraints from an ecosystem carbon cycle model. The resulting analysis quantifies, with uncertainty estimates, the seasonal changes in the net carbon flux of a tropical rainforest which experiences a pronounced dry season. We show that the carbon accumulation in this forest was four times greater in the dry season than in the wet season and that this was accompanied by a 5% increase in the carbon use efficiency. This seasonal response was caused by a dry season increase in gross primary productivity, in response to radiation and a similar magnitude decrease in heterotrophic respiration, in response to drying soils. The analysis also predicts increased carbon allocation to leaves and wood in the wet season, and greater allocation to fine roots in the dry season. This study demonstrates implementation of seasonal variations in parameters better enables models to simulate observed patterns in data. In particular, we highlight the necessity to simulate the seasonal patterns of heterotrophic respiration to accurately simulate the net carbon flux seasonal tropical forest.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)